Pulmonary papillary adenocarcinoma with Aspergillus versicolor infection in a dog - Maniam, Rathiymaler; Selvarajah, Gayathri Thevi; Mazlan, Mazlina; Than, Leslie Thian Lung (Elsevier, 2018)
Papillary adenocarcinoma of the lungs is the most common primary lung adenocarcinoma, with the feature of papillary-like structure formation by cells. A dog was presented with the primary complaint of vomiting, hyporexia and increased respiratory effort. Thoracic radiography revealed increased soft tissue radiopacity of the right cranial lung lobe suggestive of possible consolidation or collapsed lung lobe, with generalised miliary nodular pattern throughout the other lung fields. The dog was euthanized humanely and necropsy was performed. Histopathology confirmed the diagnosis of primary pulmonary lung neoplasm (papillary adenocarcinoma) with Aspergillus versicolor infection identified through fungal culture and PCR. There have been several reports on humans and dogs with fungal infections that often mimic or coexist with pulmonary neoplasm. This is the first documented report of A. versicolor isolated from a lung neoplasm in a dog in Malaysia.